Treatment with Exosomes Derived from Mesenchymal Stem Cells: A New Window of Healing Science in Regenerative Medicine - Hormozi, Arezoo; Hasanzadeh, Sajedeh; Ebrahimi, Faezeh; Daei, Narges; Hajimortezayi, Zahra; Mehdizadeh, Amir; Zamani, Majid (Current Stem Cell Research & Therapy, 2024)
Many studies have been conducted on the potential applications of mesenchymal stem cells (MSCs) over recent years due to their growing importance in regenerative medicine. Exosomes are considered cargos capable of transporting proteins, peptides, lipids, mRNAs, and growth factors. MSCsderived exosomes are also involved in the prevention or treatment of a variety of diseases, including cardiovascular diseases, neurological diseases, skin disorders, lung diseases, osteoarthritis, damaged tissue repair, and other diseases. This review attempted to summarize the importance of employing MSCs in regenerative medicine by gathering and evaluating information from current literature. The role of MSCs and the potential applications of MSCs-derived exosomes have also been discussed.
Keywords: Mesenchymal stem cells